Interaksi Sosial Siswa Berprestasi dalam Belajar - Ramanda, Peni; Syahniar, Syahniar (Konselor, 2017)
As a adolescent, smart students who are atudying in class VII junior secondary school should finalized their adolescent developmental tasks. One of the tasks that are able to foster the development of social relationships with peers as well. Fact, from the processing of Alat Ungkap Masalah Umum (AUM Umum) and sosiometri smart students have problems in social relationships with peers. The kind of research is descriptive quantitative research is 50 smart students in class VII MTsN Lubuk Buaya Padang. The instrument of this research is questioner. The result of this research is they did social interaction with individual and group as well.